The effect of exercises combined with blood flow restriction techniques on improving range of motion, pain level, and strength of the elbow joint affected by partial tears of the medial collateral ligaments in track and field athletes. - Ibrahim, L.Ammar Musa; Fayrouz, Asst.Prof.Dr. Hassanein Abdul Kadhim; Mohammed, Prof. Dr. Wissam Shallal (Sulaimani Journal for Humanities, 2026)
Elbow ligament tears are among the most common and complex injuries affecting athletes in javelin throw, shot put, tennis, golf, baseball, and handball. This injury occurs on the medial side of the elbow joint (the inner region on the side where the second wrist muscle originates). It is considered a difficult and complex injury requiring a thorough and meticulous rehabilitation period. Many athletes' careers are ended by this injury if it is not treated and rehabilitated scientifically and promptly. This study aimed to identify rehabilitation exercises that incorporate blood flow restriction techniques for elbow joint injury rehabilitation and to improve pain levels, strength, and normal range of motion in track and field athletes. The study also hypothesized that there would be statistically significant differences between the pre-test and post-test results for the study variables, favoring the post-test. The research sample consisted of four athletes with elbow ligament tears. The injury was diagnosed by a specialist physician through clinical examination and MRI. The pre-test included measuring pain levels and grip strength to assess strength. The forearm muscles were measured using a dynamometer, and the range of motion of the elbow joint was tested using a gonometer. An eight-week rehabilitation program was then implemented, incorporating a series of exercises combined with a method of restricting blood flow to the heart. The results were analyzed and discussed scientifically by presenting them in tables and using appropriate statistical methods. Improvements were observed in pain levels, elbow joint range of motion, and forearm muscle strength. Based on these results, several conclusions were drawn: pain levels improved, and strength and range of motion of the elbow joint improved significantly. Based on these conclusions, the researchers recommended the use of rehabilitation exercises combined with the method of restricting blood flow, as these accelerate the activation of forearm muscles, which in turn provides the necessary strength to the injured elbow joint